2001
DOI: 10.1515/humr.14.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of form and function of humor in adolescence

Abstract: This study investigates the use, form and function of humor for children aged 12±16 years in two dierent schools including 47 participants through interviews and 112 participants in a questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 0 publications
1
17
0
9
Order By: Relevance
“…This casts some doubt on the validity of this measure but it may simply indicate that it is only in adulthood that we can use this style of humor effectively to cope with life stress and adversity (Altshuler and Ruble 1983). In support of this point, interviews with a small sample of 12-16 year olds elicited open-ended responses to suggest that children of this age do see a use for humor as a coping tool, but only with less serious events (Führ 2001), e.g. "does not always help, not with serious things".…”
Section: Discussionmentioning
confidence: 99%
“…This casts some doubt on the validity of this measure but it may simply indicate that it is only in adulthood that we can use this style of humor effectively to cope with life stress and adversity (Altshuler and Ruble 1983). In support of this point, interviews with a small sample of 12-16 year olds elicited open-ended responses to suggest that children of this age do see a use for humor as a coping tool, but only with less serious events (Führ 2001), e.g. "does not always help, not with serious things".…”
Section: Discussionmentioning
confidence: 99%
“…This second type of humour is also positive in nature, non-detrimental to others and used to enhance the self (Martin et al 2003). This humour type is recommended for employees in improving social interactions and solving problems (Führ 2008). It is built on a prevailing positive outlook and an ability to see the funny side of events even when they are unpleasant (Mathies et al 2016).…”
Section: Literature Review 21 Humour In Customer Service Interactionsmentioning
confidence: 99%
“…For example, research has shown that self-deprecating humor is positively related to depression (Lin and Chiang 2015;Wu et al 2014), anxiety , hopelessness ) and social loneliness (Lin and Chiang 2015); other-devaluing humor is positively related to social anxiety and social loneliness ); body-language humor is positively related to energy, sleep quality, positive affect, and peer support and negatively related to fatigue, anxiety, and hopelessness ; and witty-response humor is positively related to happiness (Lin and Chiang 2015), parental support, teacher support, and peer support . In terms of the use of humor, adolescents have begun to involve the topics of sex and aggression (Führ 2001). When the above type of humor appears in adolescents' verbal interaction, it can be viewed as a type of maladaptive humor, which is a type of verbal bullying.…”
Section: The Importance and Types Of Humormentioning
confidence: 99%
“…To adapt during this period of instability and dramatic change, adolescents must develop coping strategies (Chiang et al 2011). Führ's (2001) research has found that 12-to 16-year-old adolescents in two different schools have learned to express and use humor to solve problems and participate in social activities.…”
Section: Introductionmentioning
confidence: 99%